Characterization of strawberry (Fragaria × ananassa) genotypes based upon the morphological and biochemical quality attributes grownin south-western Punjab - Singh, Pawandeep; Kour, Amardeep; Mahajan, Monika (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried during 2022–2023 at Punjab Agricultural University, Regional Research Station Bathinda, Punjab to identify superior strawberry genotypes based on morphological and biochemical traits. In the findings of the current investigation, it is evident that significant variations exist among the various strawberry genotypes. This diversity is attributed to a combination of environmental conditions and their interactions. Notably, the genotypes Camarosa, ’Douglas and Jutogh Special exhibit superior characteristics in terms of horticultural traits, particularly concerning fruit size, fruit weight, fruit number and fruit yield. However, in terms of biochemical traits, the genotype Winter Dawn has the highest TSS and total sugars, genotype Red Coat has the highest phenolics whereas maximum vitamin C was found in genotype Ofra. On the other hand, genotype Douglas gave maximum anthocyanin values. Overall, it is anticipated that the genotypes Winter Dawn, Camarosa, Douglas, and Jutogh Special are well- suited for sub-tropical conditions in Punjab concerning fruit quality. Consequently, the observed genetic diversity within the strawberry genotypes in the south-western region of Punjab holds promise for screening elite genotypes, thereby facilitating further advancements in breeding initiatives.